2007
DOI: 10.1016/j.jpsychores.2007.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Negative affectivity and social inhibition in cardiovascular disease: Evaluating type-D personality and its assessment using item response theory

Abstract: Negative affectivity and social inhibition in cardiovascular diseaseEmons, W.H.M.; Meijer, R.R.; Denollet, J. General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
149
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(157 citation statements)
references
References 47 publications
(65 reference statements)
3
149
0
5
Order By: Relevance
“…A previous study confirmed that it is the interaction of both traits, rather than the single traits, that incurs an increased risk of adverse health outcomes [23]. Recently, the cut-off score of ≥10 for both subscales has been confirmed as the most optimal by means of Item Response Theory in samples from the general population, CAD patients, and hypertensives [24]. Both of the DS14 subscales of Negative Affectivity and Social Inhibition have good internal consistency (Cronbach's α=0.88/0.86), are stable over a 3-month period (r=0.82/0.72), and are independent of mood and health status [22].…”
Section: Type D Personalitymentioning
confidence: 95%
“…A previous study confirmed that it is the interaction of both traits, rather than the single traits, that incurs an increased risk of adverse health outcomes [23]. Recently, the cut-off score of ≥10 for both subscales has been confirmed as the most optimal by means of Item Response Theory in samples from the general population, CAD patients, and hypertensives [24]. Both of the DS14 subscales of Negative Affectivity and Social Inhibition have good internal consistency (Cronbach's α=0.88/0.86), are stable over a 3-month period (r=0.82/0.72), and are independent of mood and health status [22].…”
Section: Type D Personalitymentioning
confidence: 95%
“…The DS14 comprises 14 items, contributing to two 7-item subcales, that is negative affectivity (NA; e.g., "I often feel unhappy") and social inhibition (SI; e.g., "I find to hard to start a conversation") (Denollet, 2005). Type D caseness is determined by means of a standardized cut-off ≥10, with a recent study using item-response theory showing that this is the most optimal cut-off on both subscales (Emons, Meijer & Denollet, 2007). The DS14 is a valid and reliable scale, with high internal consistency as assessed by Cronbach's alpha (NA = 0.88; SI = 0.86) and good 3-month test-retest reliability (NA: r = 0.72; SI: r = 0.82).…”
Section: Measures Type D Scalementioning
confidence: 99%
“…Type D case is defined by a score of ≥10 on both subscales, 21 with this cutoff being the most optimal according to item response theory. 22 The DS14 has good psychometric properties with Cronbach's α = 0.88/0.86 and 3-month test-retest reliability = 0.72/0.82 for the negative affect and the social inhibition subscales, respectively. 21 Type D personality is not confounded by indicators of disease PACE, Vol.…”
Section: Personalitymentioning
confidence: 96%